PERBANDINGAN KINERJA KEUANGAN PADA PT BUKIT ASAM Tbk, PT BUMA INTERNASIONAL GRUP Tbk, dan PT ADARO ENERGY INDONESIA Tbk dengan MENGGUNAKAN PENDEKATAN CROSS SECTION dan TIME SERIES - Siti Nur Reskiyawati Said (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2025)
This study aims to analyze and compare the financial performance of PT Bukit Asam Tbk (PTBA), PT BUMA International Group Tbk (BUMA), and PT Adaro Energy Indonesia Tbk (ADRO) during 2022–2024 using time series and cross-sectional approaches. The analysis covers liquidity, activity, and profitability ratios to evaluate financial stability, asset efficiency, and profitability. The results indicate that ADRO has the most stable and superior financial performance compared to PTBA and BUMA, both in terms of liquidity and profitability. PTBA shows a declining trend in liquidity and profitability, while BUMA faces significant financial risk with negative profitability ratios in 2024. The study provides insights for corporate management, investors, and stakeholders regarding the relative position of coal mining companies in Indonesia.